CD28 negative T cells are enriched in granulomatous lesions of the respiratory tract in Wegener's granulomatosis. Issue 10 (1st October 2001) - Lamprecht, P; Moosig, F; Csernok, E; Seitzer, U; Schnabel, A; Mueller, A; Gross, W L
Abstract : BACKGROUND: Lack of CD28 expression on peripheral blood CD4+ and CD8+ T cells has been reported in patients with Wegener's granulomatosis (WG), suggesting a pathogenetic role of CD28– T cells in WG. METHODS: Ten patients with WG and six with sarcoidosis (disease control) were analysed. Fluorescence activated cell sorter (FACS) analysis was used to detect CD28 expression on T cells from peripheral venous blood and from bronchoalveolar lavage (BAL) fluid. T cells in biopsy specimens from granulomatous lesions of the upper respiratory tract were analysed for CD28 expression by double immunofluorescence staining. RESULTS: A significantly higher fraction of CD28– T cells was found in the CD4+ and CD8+ T cell compartment in BAL fluid (65.6 (5.4)% and 76.3 (4.1)%, respectively) than in blood (13.4 (6.2)% and 42.9 (6.2)%; p<0.001) in patients with WG but not in those with acute sarcoidosis (6.7 (2.2)% and 53.4 (7.3)% in BAL fluid v 4.1 (2.5)% and 52.0 (9.4)% in blood). The total number of CD4+/CD28– T cells but not of CD8+/CD28– T cells was also significantly higher in BAL fluid than in blood in patients with WG (p<0.05). Patients with WG had a significantly higher fraction of CD28– T cells in the CD4+ and CD8+ T cell compartment in BAL fluid than patients with acute sarcoidosis (65.6 (5.4)% v 6.7 (2.2)%; p<0.001; and 76.3 (4.1)% v 53.4 (7.3)%; p<0.05). The total number of CD4+/CD28– and CD8+/CD28– T cells was also significantly higher in patients with WG than in those with sarcoidosis (p<0.01). An abundance of CD28– T cells was found in granulomatous lesions by double immunofluorescence staining in patients with WG. CONCLUSIONS: Our data indicate enrichment of CD28– T cells in BAL fluid and suggest recruitment of CD28– T cells into granulomatous lesions in WG. Further analysis of the phenotype and function of T cell subsets in WG is needed to better understand leucocyte homing in WG and to find new therapeutic targets.